Santa is coming to Seattle - Smallman, Steve (Sourcebooks Jabberwocky, 2015)
The Jolly Old Elf heads south from his home in the North Pole to Seattle to deliver presents and good cheer, with a little help from the youngest reindeer, and not so much from his brand-new, high-tech Santa-nav system.